Students’ Perception on Learning Language at the Graduate Program of English Education Amids the COVID 19 Pandemic - Wisma Yunita; Ira Maisarah (Islamic State Institute of Bengkulu (IAIN) Bengkulu, 2020)
This research aims to determine students' perceptions on the implementation of the learning process during the Covid 19 pandemic at the graduate program of English Education of the University of Bengkulu. This research is a descriptive research involving students in academic year of 2019/2020 from two classes consisting of 34 students. The data was taken using a questionnaire in the form of Google form consisting of 40 questions with 5 answer options: strongly agree, agree, neutral, disagree, and strongly disagree and semi-structured written interview given through the Google Classroom application. The data obtained were analyzed quantitatively and qualitatively. The results of this research indicate that students have a positive perception of the implementation of the learning process during the Covid19 pandemic the the graduate program of English Education of university of Bengkulu with the averageobtained score of 1211.25 which is in the good category. Moreover, the data obtained from the written interview showed that most students gave positive responses to online learning conducted at the graduate program of English education of the University of Bengkulu. These findings are expected to be taken into consideration to improve and prepare for the better future online and offline learning process at the University of Bengkulu, especially at the Graduate Program of English Education of the University of Bengkulu.